2021
DOI: 10.1371/journal.pone.0251236
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of point-of-care ultrasound for pulmonary tuberculosis: A systematic review

Abstract: The advent of affordable, portable ultrasound devices has led to increasing interest in the use of point-of-care ultrasound (POCUS) for the detection of pulmonary TB (PTB). We undertook a systematic review of the diagnostic accuracy of POCUS for PTB. Five databases were searched for articles published between January 2010 and June 2020. Risk of bias was assessed using QUADAS-2. Data on sensitivity and specificity of individual lung ultrasound findings were collected, with variable reference standards including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 39 publications
(67 reference statements)
1
33
0
Order By: Relevance
“… Triage Software products include: qXR (QURE.ai Technologies), CAD4TB (Delft Imaging Systems), and Lunit (FujiFILM), CAD4Good (EPCON) (see AI4HLTH for a complete overview) 30 - In a very large evaluation in Bangladesh, qXR and CAD4-TB have the highest specificities (both 73%) at >90% sensitivity 50 - Automated reading systems can overcome radiologist shortages and are WHO-endorsed 48 - Expensive equipment and infrastructure (including high-speed internet) required 52 , however, existing equipment may be retrofitted such that analogue images can be converted to digital ones - Market rapidly evolving and selection of the right solutions challenging - Challenges in identifying which settings for prioritisation, including case finding scenarios where pre-symptomatic TB can be detected 115 - Achieving adequate throughput to maximise utility is challenging - Unclear how these technologies will benefit diagnosis of other diseases - Open source social impact programs such as CAD4Good may reduce costs 30 POCUS Improving affordability and portability of ultrasound devices has led to interest in the use of POCUS. Triage Many (most standard point-of-care ultrasound machines can be used) - Systematic review reported sensitivities ranging from 73-100% for subpleural nodules detected and 47-80% for lung consolidation 54 Potential to expand diagnosis of extrapulmonary TB and increase diagnostic yield in populations such as children or PLHIV - Limited data, currently majority of studies in adults and for pulmonary TB - Effects of operator and machine variability unclear - Optimal imaging protocols unclear …”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
See 1 more Smart Citation
“… Triage Software products include: qXR (QURE.ai Technologies), CAD4TB (Delft Imaging Systems), and Lunit (FujiFILM), CAD4Good (EPCON) (see AI4HLTH for a complete overview) 30 - In a very large evaluation in Bangladesh, qXR and CAD4-TB have the highest specificities (both 73%) at >90% sensitivity 50 - Automated reading systems can overcome radiologist shortages and are WHO-endorsed 48 - Expensive equipment and infrastructure (including high-speed internet) required 52 , however, existing equipment may be retrofitted such that analogue images can be converted to digital ones - Market rapidly evolving and selection of the right solutions challenging - Challenges in identifying which settings for prioritisation, including case finding scenarios where pre-symptomatic TB can be detected 115 - Achieving adequate throughput to maximise utility is challenging - Unclear how these technologies will benefit diagnosis of other diseases - Open source social impact programs such as CAD4Good may reduce costs 30 POCUS Improving affordability and portability of ultrasound devices has led to interest in the use of POCUS. Triage Many (most standard point-of-care ultrasound machines can be used) - Systematic review reported sensitivities ranging from 73-100% for subpleural nodules detected and 47-80% for lung consolidation 54 Potential to expand diagnosis of extrapulmonary TB and increase diagnostic yield in populations such as children or PLHIV - Limited data, currently majority of studies in adults and for pulmonary TB - Effects of operator and machine variability unclear - Optimal imaging protocols unclear …”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“… 53 Other imaging technologies of interest include point-of-care ultrasound (POCUS), for which a systematic review revealed sensitivities from 73-100% for subpleural nodules and 47-80% for lung consolidation; however, data are limited with high risk of bias. 54 …”
Section: Overview Of Diagnostic Technologies and Tests By Specimen Typementioning
confidence: 99%
“…The potential of LUS in diagnosing pulmonary TB is increasingly recognized. A recent systematic review (Bigio et al 2021) showed that the presence of subpleural nodules had the highest sensitivity ranging from 73% to 100%.…”
Section: Rapid Differential Diagnosis Of Respiratory Syndromesmentioning
confidence: 99%
“…A recent systematic review calculated for TUS a sensitivity ranging from 72.5 to 100.0% in the assessment of subpleural nodules and from 46.7 to 80.4% in the detection of consolidations. On the other hand, TUS sensitivity for cavitations ranged from 4.0 to 30.0% (41).…”
Section: Parenchymal Diseasementioning
confidence: 96%